Treatment of traumatic birth experience with postpartum early eye movement desensitization and reprocessing therapy: a randomized clinical trial - Hendrix, Yvette M.G.A.; van Pampus, Maria G.; Hofman, Amy; Henrichs, Jens; van der Horst, Henriëtte E.; de Jongh, Ad (American journal of obstetrics and gynecology, 2025)
A traumatic birth experience can have negative consequences for both mother and infant, including developing (symptoms of) posttraumatic stress disorder, postpartum depression, difficulties in mother–infant bonding, fear of childbirth, or reduced quality of life. This study aimed to investigate the effectiveness and safety of early trauma-focused therapy, specifically eye movement desensitization and reprocessing therapy, in reducing symptoms and incidence of posttraumatic stress disorder at 9 weeks postpartum in women with a traumatic birth experience, compared with care as usual (controls). A randomized controlled trial was conducted in a hospital and 25 midwifery practices in Amsterdam, the Netherlands, enrolling women within 14 days postpartum who reported a traumatic birth experience. The participants received 2 eye movement desensitization and reprocessing therapy sessions of 60 minutes per session (treatment group) or 2 telephone calls (controls) between 2 and 5 weeks postpartum. The primary outcome was symptoms of posttraumatic stress disorder at 9 weeks postpartum measured by the self-report questionnaire Posttraumatic Stress Disorder Checklist for Diagnostic and Statistical Manual of Mental Disorders (cutoff ≥29 indicative of posttraumatic stress disorder) and the Clinician-Administered Posttraumatic Stress Disorder Scale for Diagnostic and Statistical Manual of Mental Disorders, a structured interview. Secondary outcomes included symptoms of depression, mother–infant bonding, fear of childbirth, quality of life, and breastfeeding rates. Of 10,963 women screened, 861 reported a traumatic birth experience and 151 participants were randomly assigned (1:1) to the treatment group (n=76) or control group (n=75). After randomization, 7 participants withdrew informed consent and 1 participant was inaccessible leaving 74 participants in the treatment group and 69 in the control group for intention-to-treat analyses. The treatment group showed a larger reduction in Posttraumatic Stress Disorder Checklist for Diagnostic and Statistical Manual of Mental Disorders, fifth edition scores than the control group (adjusted mean difference on square root scale=−0.82; 95% confidence interval, −1.24 to −4.04; P<.001; mean difference=−8.7 points). Square root transformed Clinician-Administered Posttraumatic Stress Disorder Scale for Diagnostic and Statistical Manual of Mental Disorders, fifth edition symptom severity scores were significantly lower in the treatment group (adjusted mean difference=−0.73; 95% confidence interval, −1.23 to −0.23; P=.004; mean difference=−3.8 points). The incidence of probable posttraumatic stress disorder decreased more in the treatment group (39.2% [n=29] to 11.1% [n=8]) than in controls (44.9% [n=31] to 29.2% [n=19]); adjusted odds ratio=0.32; 95% confidence interval, 0.14 to 0.73; P=.006. However, posttraumatic stress disorder diagnosis rates per Clinician-Administered Posttraumatic Stress Disorder Scale for Diagnostic and Statistical Manual of Mental Disorders, fifth edition were not significantly different between groups: 3 participants (4.2%) in the treatment group vs 6 participants (9.1%) in the control group (P=.310). Eye movement desensitization and reprocessing therapy reduced depressive symptoms (P<.001), symptoms of mother–infant bonding difficulties (P=.008), fear of childbirth (P=.001), and quality of life in the psychological domain (P=.006). No differences in breastfeeding rates were observed. Serious adverse events were not observed. Compared to controls, eye movement desensitization and reprocessing therapy proved both effective and safe in reducing symptoms of posttraumatic stress disorder and related psychological distress in postpartum women with a traumatic birth experience. Its integration into postnatal care protocols may be of great benefit to this group. [Display omitted]